3D‐Printed Acidic Monolithic Catalysts for Liquid‐Phase Catalysis with Enhanced Mass Transfer Properties. Issue 8 (1st March 2022) - Hock, Sebastian; Rein, Christof; Rose, Marcus
Abstract: The thriving research and development in additive manufacturing and especially 3D printing in chemical engineering and heterogeneous catalysis enables novel and innovative approaches for the shaping of catalysts. In this work, tailor‐made monoliths with complex transport pore channels are designed and printed by fused deposition modelling (FDM) from polystyrene filament. Subsequently, sulfonic acid groups are introduced by sulfonation for a catalytic functionalization of the structured monoliths' accessible inner surface. As a catalytic test reaction, the aqueous phase hydrolysis of sucrose was chosen. For this reaction the functionalized monoliths exhibited a superior catalytic performance in both batch and continuous reaction mode in comparison to a macroporous sulfonic acid‐functionalized ion exchange resin as commercial benchmark catalyst. This is due to the higher accessibility of the sulfonic acid groups on the surface of the monoliths' pore channels and hence, enhanced effective reaction kinetics by decreased mass transfer limitations. Abstract : In this work the versatile fused deposition modeling (FDM) is applied for the production of innovative monolithic catalysts from polymeric precursors with subsequent acid functionalization by sulfonation. The functionalized monoliths show a superior catalytic performance in batch and continuous testing compared to acidic ion exchange resins as commercial benchmark catalysts for the hydrolysis of sucrose as model reaction.